2017
DOI: 10.1007/s00204-017-2106-7
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy-based high-throughput assays enable multi-parametric analysis to assess adverse effects of nanomaterials in various cell lines

Abstract: Manufactured nanomaterials (MNMs) selected from a library of over 120 different MNMs with varied compositions, sizes, and surface coatings were tested by four different laboratories for toxicity by high-throughput/-content (HT/C) techniques. The selected particles comprise 14 MNMs composed of CeO, Ag, TiO, ZnO and SiO with different coatings and surface characteristics at varying concentrations. The MNMs were tested in different mammalian cell lines at concentrations between 0.5 and 250 µg/mL to link physical-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 68 publications
(70 reference statements)
2
44
0
1
Order By: Relevance
“…Though SYTOX staining does not allow to discriminate primary and secondary necrosis, the absence of clear Annexin V staining at 24 h (also visible in the double scatter plots shown in Supplementary Figure S1) suggested that, as opposed to what is usually observed with these nanoparticles in other cell models (Bexiga et al 2011;Wang et al 2013a, b), in MPI macrophages exposure to NH 2 -PS nanoparticles led to cell death, but not via apoptosis. This is in agreement with previous observations of necrotic cell death induced by the same nanoparticles in RAW 364.7 macrophages (Hansjosten et al 2018). On the contrary, SiO 2 nanoparticles displayed a clear apoptotic signature, with both an elevation of the percentage of apoptotic cells and increases in caspase 3/7 activity.…”
Section: Apoptosis and Necrosis After Exposure To Nanoparticlessupporting
confidence: 94%
“…Though SYTOX staining does not allow to discriminate primary and secondary necrosis, the absence of clear Annexin V staining at 24 h (also visible in the double scatter plots shown in Supplementary Figure S1) suggested that, as opposed to what is usually observed with these nanoparticles in other cell models (Bexiga et al 2011;Wang et al 2013a, b), in MPI macrophages exposure to NH 2 -PS nanoparticles led to cell death, but not via apoptosis. This is in agreement with previous observations of necrotic cell death induced by the same nanoparticles in RAW 364.7 macrophages (Hansjosten et al 2018). On the contrary, SiO 2 nanoparticles displayed a clear apoptotic signature, with both an elevation of the percentage of apoptotic cells and increases in caspase 3/7 activity.…”
Section: Apoptosis and Necrosis After Exposure To Nanoparticlessupporting
confidence: 94%
“…Characterization of NM dispersions: Dynamic Light Scattering (DLS), zeta potential, and Inductively Coupled Plasma Mass Spectrometry (ICP-MS): NM stock suspensions were diluted as per the NanoMILE protocol for the dilution and dispersion of liquid suspension NMs in the relevant medium (ultrapure H 2 O, complete-serum containing medium (SCM), and artificial lysosomal fluid) to a concentration of 125 µg/mL [46]. Each NM suspension was then incubated at 37 • C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Eine erhöhte Freisetzung von LDH, einem im Zytoplasma vorhandenen Enzym, würde auf eine Schädigung der Plasmamembran der Zellen hinweisen. Sogar bis zu einer Konzentration von 100 μg mL −1 , was gut oberhalb klinisch relevanter Dosen liegt, verstärken ROMPISA‐NPs nicht die Freisetzung von LDH (Abbildung A, rote Balken), insbesondere im Unterschied zu positiven Kontrollproben wie aminofunktionalisierten Polystyrol‐NPs . In ähnlicher Weise zeigt der WST‐1‐Test eine hohe Biokompatibilität ohne Abnahme des zellulären Metabolismus an, wodurch die extrem niedrige Toxizität unserer ROMPISA‐Nanopartikel bestätigt wird (Abbildung A, grüne Balken).…”
Section: Methodsunclassified